Extended bluetooth naming for empowered presence and situated interaction with public displays - José, Rui (2009)
The paradigm of proximity-based discovery and communication enabled by Bluetooth technology can be very relevant in Ambient Intelligence as an enabler for situated interaction. In this work, we explore the use of Bluetooth naming as a key driver for situated interaction around public displays. Our approach to the use of Bluetooth naming extends beyond self-exposure and introduces support for simple commands in the name that can trigger actions on the displays. Our specific objective is to evaluate the usability of this interaction technique and uncover any guidelines for its usage. We have conducted a study combining a trial in a public bar and a set of usability interviews. The results obtained confirm Bluetooth Extended Naming as an easily adoptable technique for situated interaction and suggest some recommendations to improve its effectiveness.